2013
DOI: 10.1103/physrevc.88.027302
|View full text |Cite
|
Sign up to set email alerts
|

Possible multiple chiral doublet bands in107Ag

Abstract: Two pairs of nearly degenerate doublet bands in 107 Ag are studied via the relativistic mean-field (RMF) theory and the multiparticle plus rotor model (PRM), which suggests these bands as two distinct sets of chiral doublet bands. For the suggested πg −1 9/2 ⊗ νh 2 11/2 and πg −1 9/2 ⊗ νh 11/2 d 5/2 configurations, the favorable triaxial deformation γ for nuclear chirality can be obtained from the configuration-fixed constrained triaxial RMF calculations. Adopting the PRM, the data available are reproduced ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 40 publications
0
52
0
Order By: Relevance
“…133 Ce [26] and 107 Ag [27], each chiral doublet structure corresponds to two lowest-lying bands with a distinct configuration. Therefore, study of the third and forth bands of the same chiral configuration is needed to answer the question of the investigated robustness.…”
Section: Mχd Inmentioning
confidence: 99%
See 1 more Smart Citation
“…133 Ce [26] and 107 Ag [27], each chiral doublet structure corresponds to two lowest-lying bands with a distinct configuration. Therefore, study of the third and forth bands of the same chiral configuration is needed to answer the question of the investigated robustness.…”
Section: Mχd Inmentioning
confidence: 99%
“…It was even demonstrated recently by Meng et al [22][23][24][25], based on adiabatic and configuration-fixed constrained triaxial covariant density functional theory (CDFT) calculations, that it is possible to have multiple pairs of chiral doublet bands in a single nucleus, and the acronym MχD was introduced for this phenomenon. The first experimental evidence for the predicted MχD has been reported in 133 Ce [26], and also possibly in 107 Ag [27].It is also interesting to study the robustness of chiral geometry against the increase of the intrinsic excitation energy, i.e. if the chiral geometry is sustained in the higher-lying bands of a certain chiral configuration.…”
mentioning
confidence: 99%
“…Such chiral doublet bands were first observed in N ¼ 75 isotones [2]. So far, more than 30 experimental candidates have been reported in the A ∼ 80, 100, 130, and 190 mass regions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].Based on constrained triaxial covariant density functional theory (CDFT) calculations, it has been suggested that multiple chiral doublet (MχD) bands can exist in a single nucleus [21][22][23][24][25][26]. The theoretical prediction of MχD bands stimulated lots of experimental efforts [27][28][29][30][31].…”
mentioning
confidence: 99%
“…Based on constrained triaxial covariant density functional theory (CDFT) calculations, it has been suggested that multiple chiral doublet (MχD) bands can exist in a single nucleus [21][22][23][24][25][26]. The theoretical prediction of MχD bands stimulated lots of experimental efforts [27][28][29][30][31].…”
mentioning
confidence: 99%
“…Subsequently, the evidence of MχD was also suggested in 107 Ag. 49 It is interesting to study the robustness of chiral geometry against the increase of the intrinsic excitation energy, i.e., whether the chiral geometry is sustained or not in the higher-lying bands of a certain chiral configuration.…”
Section: Historical Reviewmentioning
confidence: 99%